Electrode suitable for zinc-bromine flow battery and preparation method thereof
By designing titanium alloy electrodes with periodic arrangement of channels and adding nanoconductive particles, the electrodes are prepared by using the laser selection melting process, the problem of overgrowth of zinc dendrites in zinc bromine flow batteries is solved, and the battery life, efficiency and safety is improved.
Patent Information
- Application Number
- CN202411781144.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The excessive growth of zinc dendrites in zinc bromine flow batteries leads to short-circuit failure of the battery, low voltage efficiency on the bromine side of the positive electrode and easy leakage of bromine.
By designing a titanium alloy electrode with periodic arrangement of channels and adding nanoconductive particles to the electrode material, the electrode is prepared by using a laser selection melting process to form a diffusely distributed conductive potential point, reduce the degree of electrochemical polarization, and control the growth of zinc deposition.
Effectively inhibit the growth of zinc dendrites, improve the life, efficiency and safety of zinc-bromide flow batteries, and improve the energy density and cycle life of the battery.
Smart Images

Figure BDA0005172814660000071
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of zinc-bromine liquid flow batteries, and in particular to an electrode suitable for zinc-bromine liquid flow batteries and a preparation method thereof. Background technology:
[0002] As a typical representative of flow batteries, zinc-bromine flow batteries have broad application prospects in the field of distributed energy storage due to their high energy density and low electrolyte cost. However, the large-scale promotion and application of zinc-bromine batteries still faces some challenges, such as excessive growth of zinc dendrites during the zinc deposition process at the negative electrode, which leads to battery short-circuit failure due to penetration of the diaphragm; low voltage efficiency on the positive bromine side and easy leakage of bromine. To address the above problems, the life, efficiency and safety of zinc-bromine flow batteries are mainly improved through the optimization design and modification of electrode materials and electrolytes. Existing studies have shown that the growth rate of zinc dendrites is mainly related to the flow rate of the electrolyte, the current density and the characteristics of the electrode material.
[0003] The invention patent with publication number CN 118039991 A discloses a zinc-bromine flow battery electrolyte that inhibits zinc dendrites and a method for preparing the same. After adding conductive powders such as graphite powder, carbon black powder, zinc powder, and copper powder to the negative electrode electrolyte, the zinc is preferentially deposited on the powder when the powder contacts the electrode. The powder takes away the zinc element as the fluid circulates, thereby preventing or reducing the deposition of zinc on the negative electrode. ZL 201811423933.6 discloses a zinc-based battery negative electrode and its preparation and application, which uses a magnetron sputtering process to deposit one or more of metals, metal alloys, and metal oxides onto an electrode substrate under a specific atmosphere, so that it can effectively prevent serious changes in the shape of the zinc electrode, inhibit the growth of dendrites, and make the metal zinc more densely and evenly deposited, thereby improving the coulombic efficiency and cycle life of aqueous and organic zinc-based batteries. Publication number CN116344856A discloses a bipolar plate for zinc-based flow batteries and a method for preparing the same. Ferroelectric nanoparticles are added to the bipolar plate components and the ratio is adjusted. A high voltage corona is applied to promote the formation of uniform and switchable polarization inside the ferroelectric phase in the bipolar plate to guide the orderly migration of zinc ions, thereby solving the problem of zinc dendrites generated during zinc electrodeposition in the zinc-based flow battery cycle. The invention patent with publication number CN 118588954A discloses a method for preparing a modified electrode for zinc-bromine flow batteries. The patent drips or sprays carbon black quickly and evenly on the electrode surface, so that zinc can be evenly deposited on the electrode surface, effectively preventing zinc dendrites from piercing the battery separator. The method is inexpensive and can improve the energy efficiency of battery operation.
[0004] Comprehensive analysis of the current public information on the technical route of inhibiting the excessive growth of zinc dendrites in zinc-bromine flow batteries mainly focuses on the modification of electrolytes, bipolar plates and electrodes. Among them, the modification of electrodes is mainly to modify the surface of traditional carbon felt electrodes, so as to promote the uniform deposition of zinc on the electrode surface and regulate the growth direction of zinc dendrites. However, these modified electrode substrates still use conventional negative electrode materials and structures, and have limited ability to regulate the growth of dendrites. In addition, the zinc dendrites deposited disorderly on the cathode surface during the charging process have low bonding strength with the cathode and are easily detached from the cathode, causing battery energy loss, which further adversely affects the performance of zinc-bromine flow batteries. Among the many factors affecting zinc deposition, studies have shown that the electrochemical polarization phenomenon during the electrode charging process has the greatest influence on the deposition morphology of zinc. According to the Bolter-Volmer formula of overpotential and electrode current density, the overpotential and current density are in a positive linear relationship. The larger the current density, the greater the overvoltage. In the lower overvoltage range, the electrocrystallization of zinc exhibits three-dimensional instantaneous nucleation behavior. When the overvoltage continues to increase, the electrocrystallization behavior of zinc changes to a continuous nucleation model. Therefore, the present invention mainly aims to solve the problem of excessive zinc dendrite growth in zinc-bromine flow batteries by changing the electrochemical polarization behavior during the electrode charging process. Summary of the invention:
[0005] The present invention mainly solves the problems existing in the prior art by designing electrode materials and structures, reducing the electrochemical polarization degree of the electrode during the charging process, and then realizing controllable growth regulation of zinc deposition. The present invention provides an electrode suitable for zinc-bromine liquid flow battery and a preparation method thereof. The electrode proposed in the present invention is prepared by laser selective melting (SLM), and the electrode has periodically arranged pores. At the same time, by optimizing and adding nano-conductive particles in the electrode printing material, after being prepared by laser selective melting, dispersed conductive sites are formed on the surface of the periodically arranged pores of the electrode; on the basis of ensuring that the electrode has excellent strength, conductivity and corrosion resistance, it also has excellent ability to inhibit zinc dendrite growth.
[0006] The first object of the present invention is to provide an electrode suitable for a zinc-bromine liquid flow battery, wherein the electrode has periodically arranged pores, the pores are circular or square in shape, the pore size is 0.4-0.6 mm, and the interval between each pore is 0.4-0.6 mm; the electrode is prepared by using a mixture of titanium alloy matrix powder and nano-conductive particles as a material, wherein the particle size of the titanium alloy matrix powder is 15-53 μm, the titanium alloy matrix powder is selected from one of TA1, TA2 and TC4, the particle size of the nano-conductive particles is 100-200 nm, the nano-conductive particles are selected from one or more of TiN, silver and graphene, and the mass ratio of the nano-conductive particles to the titanium alloy matrix powder is 0.5%-2.0%.
[0007] The electrode substrate material selected in the present invention is titanium alloy, which can easily form a dense and highly adhesive oxide film on its surface, and can effectively resist corrosion including acid pickling, alkaline, neutral and oxidizing media, and can keep the electrode substrate from being corroded in the electrolyte of the zinc-bromine battery. Even if the surface is corroded or mechanically damaged, a dense and stable protective film can be quickly formed on its surface, thereby protecting the electrode substrate from damage.
[0008] Nano TiN in the nano conductive particles is a conductive material with metallic properties. Dispersed on the surface of the titanium electrode, it can increase the active sites of the electrode. Silver can form a conductive network on the surface of the titanium electrode to improve the conductivity of the electrode; graphene nanosheets have a unique two-dimensional structure and can also form a conductive network on the surface of the titanium electrode.
[0009] Preferably, the size of the pores is 0.5 mm, and the interval between the pores is 0.5 mm.
[0010] Preferably, the nano-conductive particles are a mixture of TiN and silver, and the mass ratio of nano-TiN to silver in the mixture is 0.8-1.2:1.
[0011] Preferably, the nano-conductive particles are a mixture of TiN and graphene, and the mass ratio of nano-TiN to graphene is 0.8-1.2:1.
[0012] More preferably, the mass ratio of nano-TiN to silver is 1:1, and the mass ratio of nano-TiN to graphene is 1:1.
[0013] The second object of the present invention is to provide a method for preparing the electrode suitable for zinc-bromine flow battery, which is prepared by laser selective melting process and comprises the following steps:
[0014] (1) According to the different conductivity of the electrode, different nano-conductive particles are added to the titanium alloy matrix powder to prepare the composite powder for the laser selective melting process;
[0015] (2) Adding the composite powder obtained in step (1) into the SLM printing equipment for printing to obtain the electrode, the printing process parameters are: laser power: 200-300W; scanning speed: 200-300mm / s; scanning spacing: 40-50μm; layer thickness 20-30μm.
[0016] For different titanium alloy composite powders, SLM printing process parameters are selected, and the size of the electrode is designed according to the required single cell plate size of the zinc-bromine flow battery, with a ratio of 10% of the single cell plate size. The structure of the prepared electrode has periodically arranged channels, and the channel shape is circular or square.
[0017] Preferably, the specific steps of step (1) are: adding nano-conductive particles and titanium alloy powder into a powder mixer, mixing at a speed of 50 to 60 rpm for 1 to 2 hours, and obtaining an electrode matrix composite powder with nano-conductive particles dispersed on the surface of the titanium alloy powder.
[0018] Preferably, the parameters of the printing process in step (2) are: laser power: 260-300 W; scanning speed: 200-300 mm / s; scanning spacing: 40-50 μm; layer thickness: 20-30 μm.
[0019] The present invention also protects a zinc-bromine liquid flow battery, using the electrode applicable to the zinc-bromine liquid flow battery as a negative electrode.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1) The present invention is based on the SLM printing process to prepare an electrode with periodically arranged three-dimensional channels, which has an extremely high specific surface area, so that a low current density is maintained during the charging process of the zinc-bromine flow battery, and zinc is deposited on the electrode surface in a three-dimensional instantaneous nucleation manner; 2) The nano-conductive particles added to the electrode material can form a conductive network with silver or graphene on the electrode surface, and nano-TiN is an active center of the conductive nucleation site. The metal zinc preferentially nucleates and grows on the conductive sites of the porous titanium metal framework, and gradually forms a dense and uniform zinc deposition layer, which effectively inhibits the growth of zinc dendrites. 3) Based on the porous skeleton structure of the electrode, the dense zinc deposition layer formed during the charging process can stably exist in the titanium framework during the discharge process, reducing the dead zinc falling off the electrode, achieving full discharge, and improving the energy density of the battery. Specific implementation method:
[0022] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0023] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.
[0024] Example 1
[0025] An electrode suitable for zinc-bromine flow battery is prepared by SLM printing process. The titanium alloy powder used in SLM is TA1 with a particle size of 15-53 μm. The nano-conductive particles are a mixture of TiN and silver. The particle size of the nano-conductive particles ranges from 100 to 200 nm. The mass percentage of nano-TiN and silver is 1:1, and the mass ratio of nano-conductive particles to titanium alloy matrix powder is 0.5%. The size of the prepared titanium electrode is 10×10×2 mm, and the structure is a frame structure with periodically arranged circular holes with an aperture of 0.5 mm. The specific steps of the preparation method are as follows:
[0026] (1) First, the above-mentioned nano-conductive particles and titanium alloy powder are added into a V-type powder mixer and mixed for 1 to 2 hours at a speed of 50 to 60 rpm to obtain an electrode matrix composite powder with nano-conductive particles dispersed on the surface of the titanium powder.
[0027] (2) The composite powder obtained in step (1) was added to the SLM printing equipment. The main parameters of the printing process were: laser power: 300 W; scanning speed: 200 mm / s; scanning spacing: 40 μm; layer thickness: 20 μm. The structure of the electrode after printing was a three-dimensional channel with a periodic arrangement of pores of 0.5 mm, and the interval between adjacent channels was 0.5 mm.
[0028] Example 2
[0029] An electrode suitable for a zinc-bromine flow battery is prepared by an SLM printing process. The titanium alloy powder used in SLM is TA2 with a particle size of 15 to 53 μm. The nano-conductive particles are a mixture of TiN and graphene nanosheets. The particle size of the nano-conductive particles ranges from 100 to 200 nm. The mass percentage of nano-TiN and graphene is 1:1, and the mass ratio of the nano-conductive particles to the titanium alloy matrix powder is 1.0%. The size of the prepared titanium electrode is 10×10×2 mm, and the structure is a frame structure with periodically arranged circular holes with an aperture of 0.5 mm. The specific steps of the preparation method are as follows:
[0030] (1) First, the above-mentioned nano-conductive particles and titanium alloy powder are added into a V-type powder mixer and mixed for 1 to 2 hours at a speed of 50 to 60 rpm to obtain an electrode matrix composite powder with nano-conductive particles dispersed on the surface of the titanium powder.
[0031] (2) The composite powder obtained in step (1) was added to the SLM printing equipment. The main parameters of the printing process were: laser power: 300 W; scanning speed: 300 mm / s; scanning spacing: 50 μm; layer thickness: 30 μm. The structure of the electrode after printing was a three-dimensional channel with a periodic arrangement of pores of 0.5 mm, and the interval between adjacent channels was 0.5 mm.
[0032] Example 3
[0033] An electrode suitable for a zinc-bromine flow battery is prepared by an SLM printing process. The titanium alloy powder used in SLM is TC4 with a particle size of 15 to 53 μm. The nano-conductive particles are a mixture of TiN and graphene nanosheets. The particle size of the nano-conductive particles ranges from 100 to 200 nm. The mass percentage of nano-TiN and graphene is 1:1, and the mass ratio of the nano-conductive particles to the titanium alloy matrix powder is 2.0%. The prepared titanium electrode has a size of 10×10×2 mm and a frame structure with periodically arranged square holes with a side length of 0.5 mm. The specific steps of the preparation method are as follows:
[0034] (1) First, the above-mentioned nano-conductive particles and titanium alloy powder are added into a V-type powder mixer and mixed for 1 to 2 hours at a speed of 50 to 60 rpm to obtain an electrode matrix powder with nano-conductive particles dispersed on the surface of the titanium powder.
[0035] (2) The composite powder obtained in step (1) was added to the SLM printing equipment. The main parameters of the printing process were laser power: 260 W; scanning speed: 300 mm / s; scanning spacing: 45 μm; layer thickness 25 μm. The structure of the electrode after printing was a periodically arranged square three-dimensional channel with a side length of 0.5 mm, and the interval between adjacent channels was 0.5 mm.
[0036] Comparative Example 1
[0037] The TA1 titanium electrode is machined without adding any nano-conductive particles.
[0038] The electrode prepared in Examples 1-3 or Comparative Example 1 was used as the negative electrode to assemble a zinc-bromine flow battery, wherein the carbon felt was used as the positive electrode, the polyethersulfone was used as the porous diaphragm, the titanium plate was used as the current collector, 3 mol / L ZnBr2 in the electrolyte was used as the active material, and 2 mol / L KBr was used as the supporting electrolyte. The positive and negative electrodes of the battery were connected to the test system and the current was measured at 40 mA / cm 2 The current density was constant current charged and discharged, and the SOC was charged to 60% and then discharged to 0.5 V. The performance test results of the flow battery with the above electrode structure were compared with the zinc-bromine flow battery using the same electrolyte and carbon felt as positive and negative electrodes, and the results are shown in Table 1 below.
[0039] Table 1
[0040]
[0041] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. An electrode suitable for a zinc-bromine flow battery, characterized in that: The electrode has periodically arranged pores, the pores are circular or square in shape, the size of the pores is 0.4-0.6 mm, and the interval between each pore is 0.4-0.6 mm; the electrode is prepared by using a mixture of titanium alloy matrix powder and nano-conductive particles as a material, wherein the particle size of the titanium alloy matrix powder is 15-53 μm, the titanium alloy matrix powder is selected from one of TA1, TA2 and TC4, the particle size of the nano-conductive particles is 100-200 nm, the nano-conductive particles are selected from one or more of TiN, silver and graphene, and the mass ratio of the nano-conductive particles to the titanium alloy matrix powder is 0.5%-2.0%.
2. The electrode for zinc-bromine flow battery according to claim 1, characterized in that: The size of the pores is 0.5 mm, and the interval between the pores is 0.5 mm.
3. The electrode for zinc-bromine flow battery according to claim 1, characterized in that: The nano conductive particles are a mixture of TiN and silver, and the mass ratio of nano TiN to silver in the mixture is 0.8-1.2:
1.
4. The electrode for zinc-bromine flow battery according to claim 1, characterized in that: The nano conductive particles are a mixture of TiN and graphene, and the mass ratio of nano TiN to graphene is 0.8-1.2:
1.
5. The electrode for zinc-bromine flow battery according to claim 3 or 4, characterized in that: The mass ratio of nano-TiN to silver is 1:1, and the mass ratio of nano-TiN to graphene is 1:
1.
6. The method for preparing an electrode suitable for a zinc-bromine flow battery according to any one of claims 1 to 5, characterized in that: The process of selective laser melting is used, which includes the following steps: (1) According to the different conductivity of the electrode, different nano-conductive particles are added to the titanium alloy matrix powder to prepare the composite powder for the laser selective melting process; (2) Adding the composite powder obtained in step (1) into the SLM printing equipment for printing to obtain the electrode, the printing process parameters are: laser power: 200-300W; scanning speed: 200-300mm / s; scanning spacing: 40-50μm; layer thickness 20-30μm.
7. The preparation method according to claim 6, characterized in that: The specific steps of step (1) are: adding nano-conductive particles and titanium alloy powder into a powder mixer, mixing at a speed of 50 to 60 rpm for 1 to 2 hours, and obtaining an electrode matrix composite powder with nano-conductive particles dispersed on the surface of the titanium alloy powder.
8. The preparation method according to claim 6, characterized in that: The parameters of the printing process in step (2) are: laser power: 260-300 W; scanning speed: 200-300 mm / s; scanning spacing: 40-50 μm; layer thickness: 20-30 μm.
9. A zinc-bromine flow battery, characterized in that: The electrode suitable for zinc-bromine flow battery according to any one of claims 1 to 5 is used as a negative electrode.
Citation Information
Patent Citations
A zinc-based battery anode and its preparation and application
CN111224115B
Bipolar plate for zinc-based flow battery and preparation method of bipolar plate
CN116344856A
Zinc-bromine flow battery electrolyte for inhibiting zinc dendrites and preparation method of zinc-bromine flow battery electrolyte
CN118039991A
Preparation method of modified electrode for zinc-bromine flow battery
CN118588954A
Porous metal electrodeposition device with in-situ measurement function and electrodeposition process of electrodeposition device
CN109402715A